Transforming Aluminum Welding Through FSW Innovations: Mengubah Pengelasan Aluminium Melalui Inovasi FSW - Sjaifulah, Sandifta Iffah; Mulyadi (Indonesian Journal of Innovation Studies, 2024)
This study explores the impact of process parameters on the macrostructure of Aluminum alloy AA6061-T651 welded via Friction Stir Welding (FSW). Using Fillet joints and hexagonal tool geometries, the study investigates variations in tool rotation speed, tool tilt angle, and depth of penetration. Results show that specimens with a tool tilt angle of 3.4° exhibit optimal macrostructural properties, including equiaxed structures and increased Mg2Si phases, enhancing mechanical properties. This research contributes valuable insights for optimizing FSW parameters in AA6061-T651 welding, with implications for improving weld quality and performance in industrial applications. Highlight: FSW affects AA6061-T651 macrostructure. Optimal parameters improve mechanical properties. Study enhances aluminum weld quality. Keyword: Friction Stir Welding (FSW), Aluminum alloy AA6061-T651, Process parameters, Macrostructure analysis, Mechanical properties